POTENSI DESA WARNA-WARNA DAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA TIGARIHIT SEBAGAI OBYEK TARIK WISATA DI KABUPATEN SIMALUNGUN - Femmy Indriani Dalimunthe (Jurnal Ilmiah Akomodasi Agung, 2021)
This study aims to determine the potential of the Colorful Village of Tigarihit Village and the extent of community participation to develop this village as a leading tourist attraction and attraction in Simalungun Regency. This is important to study because the Colorful Village of Tigarihit has the potential to develop when viewed from 3A; Attractions, accessibility and amenities. Especially if it is supported by community participation around. The study was conducted with a qualitative approach. It is designed to dig deeper into the tourism potentials of the colorful village of Tigarihit in Simalungun Regency and the extent of community participation in supporting the development of these attractions.